ICTMI 2017 Proceedings of the International Conference on Translational Medicine and Imaging - Gulyás, Balázs; Padmanabhan, Parasuraman; Fred, A. Lenin; Kumar, T. R. Santhosh; Kumar, Sundramurthy; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book highlights the latest research presented at the International Conference on Translational Medicine and Imaging (ICTMI) 2017. This event brought together the world's leading scientists, engineers and clinicians from a wide range of disciplines in the field of medical imaging. Bioimaging has continued to evolve across a wide spectrum of applications from diagnostics and personalized therapy to the mechanistic understanding of biological processes, and as a result there is ever-increasing demand for more robust methods and their integration with clinical and molecular data. This book presents a number of these methods.
1.Brain tumor detection and classification of MRI brain images using morphological operations -- 2. Nir Reflectance Imaging of Biological Tissue Using Multiple Sources and Detectors -- 3. Feature Extraction Based Hyperspectral Unmixing -- 4.An Automated Framework for Prediction of Falls in Cardiomyopathy People -- 5.Synthesis, Characterization and MRI Properties of Cysteamine Stabilized Cadmium Zinc Selenide (Cd(Zn)Se) Quantum Dots for Cancer Imaging -- 6. Measures of Diffusion Tensor Tractography of regions associated with Default Mode Network in Alzheimer's Disease.
Keywords: Biomedical engineering; Cancer; Medical physics; Biomaterials; Medicine -- Research; Biology -- Research; Signal processing; Biomedical Engineering and Bioengineering; Cancer Biology; Medical Physics; Biomaterials; Biomedical Research; Signal, Speech and Image Processing .